Study of Universal Ideas About a Perfect Man in The Poetry of Khoja Ahmad Yassavi (Journal of Pedagogical Inventions and Practices, 2023)
In this scientific article, in the philosophical analysis of the study of universal ideas about the perfect person in the poetry of Khoja Ahmad Yassavi, it is shown that the teachings of Sufism began to spread in the second half of the 12th century, the great teachers of him, Yusuf Hamadoni, his students, such as Khoja Abdulkhaliq Ghijduvani, Khoja Ahmad Yassavi noted that his service was great in this field. Ahmad Yassavi's poetry is the most popular, people-loving, right-loving poetry. Socialphilosophical, universal ideas about the wisdom of the thinker are researched in this article in a unique way.